Iatrogenic Intravascular Foreign Body Retrieval in a Neonate - Manish Kumar Yadav; Ramakrishna Pillai; Madhavan Unni; Shaji Palangadan; Naveen Jain (Journal of Clinical Interventional Radiology ISVIR)
This is a short communication demonstrating a unique method of intravascular foreign body retrieval by grasp from inside technique in a neonate.